World and words: the limits to Mimesis and immersion in Heliodorus’ Ethiopica - Grethlein, Jonas (Experience, narrative, and criticism in ancient Greece, 2020)
This chapter considers the Ethiopica’s piercing reflections on narrative mimesis that can be found in the responses to embedded narrations and other passages. The Ethiopica certainly emphasize the capacity of narrative to enwrap the audience, but at the same time they do not fail to mark the limits to immersion. As parallels in ekphrastic literature and the theory of rhetoric indicate, this play with immersion and reflection bespeaks a broader sensitivity to the complex nature of aesthetic experience in the Imperial Age. Heliodorus also draws our attention to the different perspectives of readers and characters no matter how experiential the narrative is. Embedded audiences highlight the dynamics of narrative economy which privileges readers over characters. Moving from reception to the medium of narrative, one finds implicit reflections on the ontological and epistemological gap between words and the world they represent. The chapter yields the conclusion that Heliodorus artfully entwines immersion and reflection, therefore ironically providing a corrective to the post-structuralist assumptions that have guided some of the most fruitful explorations of the Ethiopica.
Gesehen am 22.07.2020